THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY, INTELLECTUAL CAPITAL, AND CAPITAL STRUCTURE ON FIRM VALUE WITH PROFITABILITY AS INTERVENING VARIABLE (STUDY OF RAW MATERIAL AND MANUFACTURING PRODUCING SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHAN - Amry Mahdan Abrari; Heri Pratikto; Ely Siswanto (Pusat Riset dan Inovasi Nasional, 2022)
Firm value is the investor's perception of the company's success in managing the company's resources. Companies are required to think effectively and efficiently and excel in competition. To increase the value of the company, all companies must compete; this study aims to determine the direct and indirect effects of corporate social responsibility, intellectual capital, and capital structure on firm value through profitability in companies in the raw material-producing sector and the manufacturing industry on the Indonesia Stock Exchange for 2016- 2020. This study uses a quantitative descriptive, explanatory approach. The sampling population is companies that are members of the raw material producing and manufacturing sector companies. The sampling technique used was purposive sampling. Research samples were obtained from 16 companies. The type of data used is secondary data. The data analysis technique used path analysis with the help of SPSS version 25. The results showed that corporate social responsibility, intellectual capital, and capital structure had a positive and significant effect on profitability. Corporate social responsibility, intellectual capital, capital structure, and profitability positively and significantly impact firm value. Profitability can mediate the development of corporate social responsibility, intellectual capital, and capital structure on firm value. This study found that profitability can judge the effect of corporate social responsibility, intellectual capital, and capital structure on company value in companies listed on the Indonesia Stock Exchange in 2016-2022